2022
DOI: 10.3390/cancers14051321
|View full text |Cite
|
Sign up to set email alerts
|

Direct Targeting KRAS Mutation in Non-Small Cell Lung Cancer: Focus on Resistance

Abstract: KRAS is the most frequently mutated oncogene in non-small cell lung cancers (NSCLC), with a frequency of around 30%, and encoding a GTPAse that cycles between active form (GTP-bound) to inactive form (GDP-bound). The KRAS mutations favor the active form with inhibition of GTPAse activity. KRAS mutations are often with poor response of EGFR targeted therapies. KRAS mutations are good predictive factor for immunotherapy. The lack of success with direct targeting of KRAS proteins, downstream inhibition of KRAS ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…More than 50% of the patients treated with sotorasib and adagrasib do not show significant tumor reduction when treated with these specific KRAS G12C inhibitors [ 140 , 141 , 142 , 143 ]. Moreover, resistance to these molecules occurred relatively early, most of the time a few months following the treatment initiation [ 139 ].…”
Section: Resistance Mechanisms Induced In Non-small Cell Lung Carcino...mentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50% of the patients treated with sotorasib and adagrasib do not show significant tumor reduction when treated with these specific KRAS G12C inhibitors [ 140 , 141 , 142 , 143 ]. Moreover, resistance to these molecules occurred relatively early, most of the time a few months following the treatment initiation [ 139 ].…”
Section: Resistance Mechanisms Induced In Non-small Cell Lung Carcino...mentioning
confidence: 99%
“…Therefore, recent clinical data showed that the duration of response for the great majority after sotorasib treatment is quite short, since the median progression-free survival is around 6 months [ 23 ]. These different results stress the urgent need to better characterize the resistance pathways that can be induced by the KRAS G12C inhibitors [ 139 , 142 ]. In fact, different mechanisms of primary and secondary resistances occurring in KRAS -mutated NSCLC patients treated with these inhibitors can explain these clinical results ( Figure 2 ) [ 141 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 ].…”
Section: Resistance Mechanisms Induced In Non-small Cell Lung Carcino...mentioning
confidence: 99%
“…Therefore, it should be hypothesized that the KRAS-activated signal might lead to the avoidance of the growth-inhibitory effects of butyrate. Although no direct experimental reports evaluate the role of SCFA in the lung epithelium, the observations made on the gut should be of potential interest also in the NSCLC context, since KRAS genetic changes are frequently detected in those tumors aroused in smoker subjects and might be kept under consideration in treatment design and approach [58][59][60]. Smoke affects bacteria in different ways [61].…”
Section: Genetic Signatures On Microbiota and Effect Of Microbiota On...mentioning
confidence: 99%
“…The table below shows the anti-tumor activity of Compound 1 compared to that of a single agent (erlotinib or cetuximab) dosed alone or in combination in nude mice with human NCI-H2122 NSCLC xenograft tumors, where Cl = confidence interval and TGI = tumor growth inhibition. …”
Section: Important Compound Classesmentioning
confidence: 99%